АНГЛИЧАН ӘДЕБИЯТЫ ҲӘМ БАЙРОН ПОЭЗИЯСЫНА ЖОЛ - Тәжиева, А.; Мухаммадияров, А. (FAN va JAMIYAT, 2017)
The article deals with the description of the life and creative work of the famous English poet-classic George Gordon Byron. The author of the article shows the place and importance of the poet’s creative work in Uzbek and Karakalpak poetry.